Synthesis and Characterization of Silica-Coated Oxyhydroxide Aluminum/Doped Polymer Nanocomposites: A Comparative Study and Its Application as a Sorbent - Inas A. Ahmed; H. S. Hussein; Ahmed H. Ragab; Najlaa S. Al-Radadi (Molecules, 2020)
The present investigation is a comparison study of two nanocomposites: Nano-silica-coated oxyhydroxide aluminum (SiO2–AlOOH; SCB) and nano-silica-coated oxyhydroxide aluminum doped with polyaniline (SiO2–AlOOH–PANI; SBDP). The prepared nanocomposites were evaluated by monitoring the elimination of heavy metal Ni(II) ions from aquatic solutions. The synthesized nanocomposites were analyzed and described by applying scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR) techniques, as well as Zeta potential distribution. In this study, two adsorbents were applied to investigate their adsorptive capacity to eliminate Ni(II) ions from aqueous solution. The obtained results revealed that SBDP nanocomposite has a higher negative zeta potential value (−47.2 mV) compared with SCB nanocomposite (−39.4 mV). The optimum adsorption was performed at pH 8, with approximately 94% adsorption for SCB and 97% adsorption for SBDP nanocomposites. The kinetics adsorption of Ni ions onto SCB and SBDP nanocomposites was studied by applying the pseudo first-order, pseudo second-order, and Mories–Weber models. The data revealed that the adsorption of Ni ions onto SCB and SBDP nanocomposites followed the pseudo second-order kinetic model. The equilibrium adsorption data were analyzed using three models: Langmuir, Freundlich, and Dubinin–Radusekevisch–Kanager Isotherm. It was concluded that the Langmuir isotherm fits the experimental results well for the SCB and SBDP nanocomposites. Thermodynamic data revealed that the adsorption process using SCB nanocomposites is an endothermic and spontaneous reaction. Meanwhile, the Ni ion sorption on SBDP nanocomposites is exothermic and spontaneous reaction.